Problems of Sustainable Development of Single-Industry Towns. Example of Karaganda Region - MAIMURUNOVA, Akmaral; KAZBEKOV, Turlybek; MYRZABEK, Zhanat; SHUGAIPOVA, Zhanna; SAPAROVA, Botagoz; ZHUGUNISSOVA, Zhanargul (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022, 2022)
The article discusses the features and problems of mono-industrial cities in terms of sustainability on the example of the Karaganda region. The results of various studies of the existing socio-economic problems of single-industry towns and promising directions for their further development are considered, taking into account the labor and economic potential, as well as natural advantages. It was revealed that the problems of sustainability of industrial single-industry towns are typical for many countries of the Soviet Union, and therefore, this experience can be used in solving such problems. On the example of single-industry towns in the Karaganda region and the analysis of the structure of territorial and economic activity, the article describes the features of socio-economic development and their impact on the sustainable development of the region. The study also substantiates the approach to monitoring the socio-economic growth of mono-industrial economies, considering the relationship between investment in fixed assets and business activity on the basis of the calculations of the Cobb-Douglas production function.